Examining the Relationship Between Emotion Regulation Difficulties and Marital Burnout With the Mediating Role of Intimacy Styles in Couples Applying for Divorce - Tayebi , Toktam; Vatankhah, Hamidreza; Jadidi , Hooshang (Applied Family Therapy Journal (AFTJ), 2026)
Objective:  The objective of this study was to examine the structural relationships between emotion regulation and marital burnout with the mediating role of intimacy styles among couples seeking divorce.Methods and Materials: This applied study employed a descriptive–correlational design using structural equation modeling. The statistical population consisted of 500 individuals (250 couples) applying for divorce who referred to the Dispute Resolution Councils of Robat Karim and Parand in 2025, from whom participants were selected through convenience sampling. Data were collected using the Difficulties in Emotion Regulation Scale (DERS), the Marital Intimacy Scale (MIS), and the Couple Burnout Measure (CBM). Data analysis was conducted using SPSS and AMOS (Version 24). Model fit was evaluated through multiple indices including CMIN/DF, GFI, CFI, NFI, and RMSEA. Reliability was assessed using Cronbach’s alpha coefficients.Findings: Structural equation modeling indicated that emotion regulation had a significant positive effect on intimacy styles (β = 0.289, p < .001) and a significant negative direct effect on marital burnout (β = −0.221, p < .001). Intimacy styles exerted a significant negative effect on marital burnout (β = −0.259, p < .001). Bootstrap analysis confirmed that intimacy styles significantly mediated the relationship between emotion regulation and marital burnout (indirect effect β = −0.075, p = .009), with a total effect of β = −0.296.Conclusion: The findings demonstrate that difficulties in emotion regulation substantially increase marital burnout both directly and indirectly through the erosion of marital intimacy, highlighting intimacy as a critical mechanism linking emotional processes to relational deterioration in divorce-seeking couples.